2021
DOI: 10.3390/jpm11080766
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Electrophysiological Parameters, Lymphocyte Distribution and Cytokine Levels in Patients with Chronic Demyelinating Inflammatory Polyneuropathy

Abstract: The goal of this study was to analyse, in relation to electrophysiological results, the distribution of lymphocyte subpopulations and the level of cytokines in patients with the typical form of chronic demyelinating inflammatory polyneuropathy (CIDP) before immunoglobulin treatment. The study group consisted of 60 patients (52 men, eight women), with a mean age 64.8 ± 11.2, who fulfilled the diagnostic criteria for the typical variant of CIDP, with (23 patients) and without (37 patients) diabetes mellitus. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…In our study, CD3 + T cells were significantly decreased in CIDP patients with IVIg or steroid treatment compared to the untreated group, as previously reported [ 24 , 33 ]. By contrast, immune treatments failed to make a significant reversion in B-cell dysregulation in our CIDP patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, CD3 + T cells were significantly decreased in CIDP patients with IVIg or steroid treatment compared to the untreated group, as previously reported [ 24 , 33 ]. By contrast, immune treatments failed to make a significant reversion in B-cell dysregulation in our CIDP patients.…”
Section: Discussionsupporting
confidence: 90%
“…TNF-α exerts toxic effects on myelin and Schwann cells by increasing vascular permeability and breaking the blood-nerve barrier [ 42 ]. Compatible with our findings, some previous studies also reported increased serum TNF-α levels in CIDP by ELISA [ 33 , 42 , 43 ] and a relationship between disease severity and TNF-α levels [ 43 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Electrophysiological parameters in CIDP patients were also found to be closely related to the autoimmune process. All these studies may contribute to a better understanding of the pathomechanism of CIDP [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNF-α) was the most studied cytokine, measured in 383 CIDP patients across 20 studies, with 18 including control subjects 15,17,18,25,29,34,35,42,43,44,45,49,50,56,60,63,65,67 and 2 without. 40,54 In 50% of the studies involving 251 tested CIDP patients, 15,25,29,34,35,50,63,49,44 TNF-α levels were found to be elevated compared to controls.…”
Section: Tumor Necrosis Factor Alphamentioning
confidence: 99%